Pengaruh Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Pengendara Motor dan Mobil di Era Pandemi - Revi Arfamaini revi; Vedelia Brenda Harianto Vedelia (Publikasi Indonesia, 2022)
Along with the spread of Covid-19 throughout the world, all aspects of life that we are used to living, are forced to undergo changes. Therefore, the government includes the taxation sector, if it is drawn from the perspective of tax compliance itself. One of the taxes that is the biggest contributor to local tax revenues is the Motor Vehicle Tax. Motor vehicle tax is one of the tax revenues that affects the high regional income. The purpose of the study was to empirically examine the effect of taxpayer awareness, tax service quality, income level, tax knowledge, and tax sanctions on taxpayer compliance with motorbikes and cars in the pandemic era at the South Surabaya Samsat. Quantitative and explanative research methods, using non-propability sampling with accidental sampling classification to test whether taxpayer awareness, tax service quality, income level, tax knowledge, and tax sanctions on taxpayer compliance with motorbikes and cars in the pandemic era at the South Surabaya Samsat, and to test whether the predetermined hypothesis is accepted or rejected. Collecting data using a questionnaire with a sample of 100 taxpayers. Data analysis was performed with multiple linear regression. The results showed that the variables of taxpayer awareness, tax service quality, income level, tax knowledge did not have a significant but positive effect, while the tax sanctions variable had a significant and positive effect on paying motorbike and car taxes in South Surabaya Samsat